Design and synthesis of resin-attachable spatane analog for prevention of sea urchin-induced seaweed loss - Tanaka, Saki; Kuse, Masaki (Agriculture and Natural Resources, 2025)
Importance of the work: This study addresses a critical environmental issue with an innovative, potentially sustainable solution. By providing hope for restoring essential coastal ecosystems, it underscores the potential positive impact of research on the environment. Objectives: To create a new spatane-type diterpenoid analog for attachment to polymers to prevent rocky-shore denudation. Materials and Methods: The strategy utilized the method of Salomon et al. (1991) to build a spatane framework and then transform it into a target non-natural compound, as an innovative approach in the field. The methodology involved altering the spatane framework to include a methylene chain featuring a terminal alkyne, which should be of interest to researchers. Results: A [2+2] photocycloaddition reaction was achieved between 3-methylcyclopent-2-en-1-one and (1R*,2R*,4R*)-bicyclo[2.2.1]hept-5-en-2-yl acetate to construct the core structure of the spatane diterpenoid. This reaction was efficient and laid the foundation for subsequent modifications. Through a series of reactions, including Jones oxidation, Baeyer-Villiger oxidation, and reduction using DIBAL, the key intermediate compound (23) was synthesized successfully, containing the desired spatane framework and a functional group suitable for further transformation. Main finding: The spatane core structure was synthesized successfully and efficiently via a [2+2] photocycloaddition reaction, demonstrating the feasibility of creating a novel spatane-type diterpenoid analog to deter sea urchin grazing, instilling confidence in potential further related research.